Constructing world society: international organizations, otherhood and the rise of global reporting. Issue 2 (17th February 2021) - Zapp, Mike
ABSTRACT: Global reporting by international organizations (IOs) has become a widespread phenomenon in a range of policy sectors. This article analyses an original dataset of N  = 110 explicitly global reports from the period 1947–2019. Results show a striking increase in reports since the 1990s for all sectors and types of reports. In particular, reports addressing social entities (e.g. the world's children) and issues such as human development are most prevalent. Further within-report analyses show that more recent reports now routinely aggregate to the world level. I argue that this aggregation is indicative of intensified (yet not unthreatened) efforts to construct an 'imagined world society' through IOs' otherhood, i.e. their agency for other actors, principles, and entities.